2019
DOI: 10.22416/1382-4376-2019-29-3-38-48
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Bacterial Overgrowth Syndrome as a Risk Factor for Ventricular Tachycardia in Chronic Heart Failure with Left Ventricular Systolic Dysfunction

Abstract: Aim. To identify the relationship between rhythm disturbances, including ventricular tachycardia (VT), and the small intestinal bowel bacterial overgrowth syndrome in chronic heart failure (CHF) with left ventricular systolic dysfunction. Materials and methods. The study included 60 patients with CHF with systolic dysfunction of the left ventricle (left ventricular ejection fraction less than 50 %). Conventional biochemical and hematological tests , ECG and echocardiography were performed. The level of the N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…Наши результаты согласуются с данными Фадеевой М. В. и др. (2019), показавшими, что СИБР может служить дополнительным фактором риска ЖТ [30]. Принципиальная разница заключается в том, что избыточная продукция метана вызвана не избыточным бактериальным ростом, а чрезмерным ростом архей.…”
Section: кардиоваскулярная терапия и профилактика 2023;22unclassified
“…Наши результаты согласуются с данными Фадеевой М. В. и др. (2019), показавшими, что СИБР может служить дополнительным фактором риска ЖТ [30]. Принципиальная разница заключается в том, что избыточная продукция метана вызвана не избыточным бактериальным ростом, а чрезмерным ростом архей.…”
Section: кардиоваскулярная терапия и профилактика 2023;22unclassified
“…Another study also reported higher SIBO incidence in HF than in controls (41.7% vs 9.1%; OR = 7.14) but found that SIBO in HF was not associated with the New York Heart Association functional class, echocardiographic data, number of supraventricular and ventricular extrasystoles, or indicators of complete blood count or biochemical blood analysis. However, patients with SIBO had higher C-reactive protein levels and ventricular tachycardia incidence (OR = 6.8; 95%CI: 1.5-30.2) compared with those without[ 149 ].…”
Section: Heart Failurementioning
confidence: 99%